Level teaching of the English language within the framework of the updated content of secondary education in the Republic of Kazakhstan - Zhorabekova, D.M.; Tleuzhanova, G.K.; Litovkina, A.T. (KU Publ., 2021)
This article aims at analysing the way that compulsory schools in Kazakhstan approach the level based teaching of the English language in the framework of the updated content of secondary education. English language teaching is changing its paradigm in favor of level education, which is theoretically justified, and this transition in education became possible thanks to the consolidation of the experience of foreign countries and our own domestic experience. This study provides an overview of the existing policy in English language teaching, it gives an insight into the implementation of the new program taking into consideration language learning curricula or guidelines, teachers’ qualifications, textbooks, examinations, and syllabuses. This study is an attempt to analyze the process of transition to level teaching of the English language within the framework of the updated content of education in the Republic of Kazakhstan, using the available data on the language policy of Kazakhstan, regulatory documents in the sphere of language education. The results of the study show that the transition to level teaching of the English language can be successful if certain scientific and methodological conditions are met. The research results are presented in the form of a case study report, taking into account the factors that positively or negatively affect the process of implementing the language program.
Қазақстан Республикасындағы орта білім берудің жаңартылған мазмұны аясында ағылшын тілін деңгейлік оқыту
Уровневое обучение английскому языку в рамках обновленного содержания среднего образования в Республике Казахстан
Keywords: level language teaching; Common European Framework of Reference for Languages; activity approach; assessment system; language competences; competence-based approach; activity-oriented approach; trilingualism